Potential Mechanisms for Traditional Chinese Medicine in Treating Airway Mucus Hypersecretion Associated With Coronavirus Disease 2019 - Zhang, Yuanfeng; Wang, Zheyi; Zhang, Yue; Tong, Hongxuan; Zhang, Yiling; Lu, Tao (Frontiers in Molecular Biosciences, 2020)
Abstract：The rapid development of coronavirus 2019 (COVID-19) pandemic has become a great threat to global health. Its mortality (>5% WHO) is associated with inflammation related airway mucus hypersecretion and dysfunction of expectoration; and the subsequent mucus blockage of the bronchioles at critical stage is attributed to hypoxemia, complications, and even death. Traditional Chinese medicine (TCM) has rich experience in expectorant, including treatment of COVID-19 patients with airway mucus dysfunction, yet little is known about the mechanisms. This study is aiming to explore the potential biological basis of TCM herbal expectorant for treating COVID-19. Objective To get core herbs with high-frequency applications in the actions of expectoration by using association rule algorithm, and to investigate the multi-target mechanisms of core herbs in expectorant formulae for COVID-19 therapies. Methods 765 prescriptions for expectorant were retrieved from Chinese Herbal Prescription Database. The ingredient compounds and targets of core herbs were collected from TCMSP database, GeneCards and NCBI. The protein interaction network (PPI) was constructed by SRING, and the network analysis was done by Cytoscape software. Bioconductor was applied for functional enrichment analysis of targets. Results The core herbs of expectorant could regulate core pathways (MAP kinase activity, Cytokine receptor binding, G protein coupled receptor binding, etc.) via interactions of ingredients (Glycyrol, Citromitin, etc.,) on Mucin-family to eliminate phlegm. Conclusion TCM herbal expectorant could regulate MAPK and Cytokine related pathways, thereby modulating Mucin-family to affect phlegm generation and clearance, and eventually retarding the deterioration of COVID-19 disease.